ERP jako narzędzie wdrożenia podejścia procesowego do controllingu MŚP - Kluge, Paul-Dieter (Introducing ERP as a Tool for Process Oriented Controlling of Small and Medium-Sized Businesses, 2009)
Most small businesses keep track of their activities. However, they do not apply controlling tools, especially in critical situations. ERP is a tool that enables the introduction of processes orientated conception. Showing examples of activity based costs and return per customer calculations as well as their integration in the planning process, this paper explains various ways to implement controlling tools at low expense. Practical examples illustrate the theoretical part of the article. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 233-239